Fatal forecast : an incredible true tale of disaster and survival at sea - Tougias, Mike, 1955- (New York : Scribner, 2007)
Chronicles the dramatic true account of the crews of the fishing vessels Fair Wind and Sea Fever, who in 1980 were caught by a deadly Cape Cod storm that resulted in a tenacious three-day struggle for survival
Keywords: Boating accidents -- New England; Storms -- New England